2002
DOI: 10.1055/s-2002-32899
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene Lactone Glycosides, Eudesmanolides, and Other Constituents from Carpesium macrocephalum

Abstract: Two new sesquiterpene lactone glycosides and two new eudesmanolides, along with twelve known compounds were isolated from seeds of Carpesium macrocephalum. The structures of these new compounds were elucidated as 2alpha- O-beta- D-glucopyranosyl-5alpha, 11alpha H-eudesma-4(15)-en-12,8beta-olide ( 1), 2alpha- O-beta- D-glucopyranosyl-5alpha H-eudesma-4(15),11(13)-dien-12,8beta-olide ( 2), 2alpha-acetoxy-5alpha-hydroxy-11alpha H-eudesma-4(15)-en-12,8beta-olide ( 3) and 2alpha,5alpha-dihydroxy-11alphaH-eudesma-4(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 9 publications
1
46
0
Order By: Relevance
“…Thus, compound 2 was deduced to possess an 11 (13) (1) and HÀC(7) were overlapping, it is difficult to measure the coupling constants of HÀC (7) and HÀC(1). However, the Me(14) gave a strong cross-peak to HÀC(1) or HÀC (7), and a molecular model of this molecule showed that HÀC(7) was far from the Me(14), indicating a-orientation for HÀC (1). This was further confirmed by a correlation between HÀC(1) and HÀC (5).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, compound 2 was deduced to possess an 11 (13) (1) and HÀC(7) were overlapping, it is difficult to measure the coupling constants of HÀC (7) and HÀC(1). However, the Me(14) gave a strong cross-peak to HÀC(1) or HÀC (7), and a molecular model of this molecule showed that HÀC(7) was far from the Me(14), indicating a-orientation for HÀC (1). This was further confirmed by a correlation between HÀC(1) and HÀC (5).…”
mentioning
confidence: 65%
“…To study the influences that C. cernuum imposes on its environment concerning chemical aspects, as well as to search for further biologically active sesquiterpenoids from natural sources, we have reinvestigated the chemical constituents of C. cernuum. Interestingly, in our study, we have not detected germacrane sesquiterpenes, always found in the genus, which play a central role in the biosynthesis of guaiane-and eudesmane-type sesquiterpenes, but isolated a new eremophilenolide, 6b-hydroxy-8a-ethoxyeremophil-7(11)-en-12,8b-olide (1), and a new guaianolide, 4b,10b-dihydroxy-1aH,5aH,11aH-guaian-12,8b-olide (2), along with 22 known sesquiterpenoids, i.e., 4b,10b-dihydroxy-1aH,5aH-guai-11(13)-en-12,8a-olide (3) [6], 4a,10a-dihydroxy-1bH,5bH-guai-11(13)-en-12,8a-olide (4) [6], 1-epiinuviscolide (5) [15], 4a,5a-epoxy-10aH-1-epiinuviscolide (6) [9], 8-epiconfertin (7) [9], confertin (8) [15], 4H-xanthalongia (9) [16], xanthalongia (10) [16], carabone (11) [17], carabrol (12) [17], isoalantolactone (13) [11], telekin (14) [17], ivalin (15) [17], 11(13)-dihydrotelekin (16) [17], 2a-O-b-d-glucopyranosyleudesm-4(15)-en-12,8b-olide (17) [7], 2a,5a-dihydroxy-11aH-eudesm-4(15)-en-12,8b-olide (18) [7], 4(15)-bepoxyisotelekin (19) [18], alantolactone (20) [11], 11(13)-dihydroalantolactone (21) [11], caryolane-1,9b-diol (22) [19], (þ)-(S)-dehydrovomifoliol (23) [20], and (3S,5R,6S,7E)-5,6-epoxy-3-hydroxymegastigm-7-en-9-one (24) [20]. To the best of our knowledge, among these known sesquiterpenolides, compounds 3 -10 and 19 have been previously reported in some studies, but not for the species C. cernuum.…”
mentioning
confidence: 99%
“…in 2002 and. In this plant, the common structures mentioned above are expected, but eudesmanolides (12 and 14) unexpectedly contain an acetylated hydroxyl group at the C-2 position; whether the acetylised hydroxyl influences their pharmacological activities remains unknown (Yang et al, 2002a(Yang et al, , 2003a. Several eudesmanolides (18 À 23) were isolated from Carpesium divaricatum Sieb.…”
Section: Sesquiterpenoidsmentioning
confidence: 93%
“…& Sav. Their structures were elucidated as 2α-O-β-D-glucopyranosy-5α,11αH-eudesma-4(15)-en-12,8β-olide (26) and 2α-O-β-D-glucopyranosy-5αH-eudesma-4(15),11(13) dien-12,8-olide (27) by spectral methods (Yang et al, 2002b).…”
Section: Sesquiterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation